2002
DOI: 10.1209/epl/i2002-00190-3
|View full text |Cite
|
Sign up to set email alerts
|

On the consequences of the uncertainty principle on the superconducting fluctuations well inside the normal state

Abstract: We first argue that the collective behaviour of the Cooper pairs created by thermal fluctuations well above the superconducting transition temperature, T C , is dominated by the uncertainty principle which, in particular, leads to a welldefined temperature, T C , above which the superconducting coherence vanishes. On the grounds of the BCS approach, the corresponding reduced-temperature, ε C ≡ ln(T C /T C ), is estimated to be around 0.55, i.e., above T C ≃ 1.7 T C coherent Cooper pairs cannot exist. The impli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
132
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(155 citation statements)
references
References 12 publications
22
132
1
Order By: Relevance
“…This effect has been interpreted in terms of the shrinkage, induced by the magnetic field, of the superconducting wave-function to lengths of the order of the Cooper pairs size perpendicular to the applied field. 17,18 Due to the high H C2 (0) value (∼ 17 T) ∆M /H does not vanish even for the highest magnetic fields used in the experiments.…”
Section: Experimental Details and Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect has been interpreted in terms of the shrinkage, induced by the magnetic field, of the superconducting wave-function to lengths of the order of the Cooper pairs size perpendicular to the applied field. 17,18 Due to the high H C2 (0) value (∼ 17 T) ∆M /H does not vanish even for the highest magnetic fields used in the experiments.…”
Section: Experimental Details and Resultsmentioning
confidence: 95%
“…16 The lines are the normal-state or background contributions, M B (T ) H , obtained by fitting a Curie-like function [M B (T ) H = a + bT + c/T ] in the temperature region between ∼ 11 K (∼ 1.5T C ) and ∼ 20 K (∼ 2.8T C ). The lower limit corresponds to a temperature where the fluctuation effects are expected to be negligible, 17 while the upper limit is well below T CDW . As it may be already seen in this figure, the effect of the superconducting fluctuations is clearly anisotropic, being more pronounced for H ⊥ ab.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…9,19 Very recently 36 it was suggested that the physical meaning of the "total energy" cut-off follows from the uncertainty principle, which impose a limit to the confinement of the superconducting wave function. It must be however mentioned that in the critical fluctuation region, the two cut-off prescriptions almost coincide quantitatively, due to the low reduced-temperature value ε with respect to the factor c.…”
Section: Solutions With Consideration Of the Uv Cut-offmentioning
confidence: 99%
“…1 of this Comment. We have used s = c/2, and for the total-energy cutoff parameter [10,11] ε C = 0.5, which is close to the value estimated in the BCS scenario [11]. For the remaining parameter, ξ c (0), we have used the same value as proposed in Ref.…”
mentioning
confidence: 99%
“…[9] to [11] for optimally doped YBa 2 Cu 3 O 6+x ). The resulting ∆σ SF (T, 0) is the upper solid curve in Fig.…”
mentioning
confidence: 99%